Learning - Grugulis, Irena (Henry Stewart Talks, 2011)
Myths about work, Positive reasons to train and learn, organisational and individual, Success stories, Problems and nature of skill, Standardisation, routines and limits to discretion, What is happening to jobs?, Implications for the future